Correctly Distribute The Time Of The Younger Generation And Give Them The Right Direction In Choosing Their Future Profession Or Their Craft, And Cite The Factors Of Employment - Bozorova Gulnora Gulyamovna (Genius Journals, 2023)
This article is mainly based on the concepts that young people are able to properly distribute their time in addition to others, employment, the mayor at work, not being idle
Keywords: Lifestyle; hobbies; time management